A retrospective study of dual-energy CT for clinical detecting of metastatic cervical lymph nodes in laryngeal and hypopharyngeal squamous cell carcinoma. (July 2015) - Liang, Hui; Li, Aiyin; Li, Yunfeng; Cheng, Hongxia; Zhao, Qiang; Li, Jun; Wang, Qirong
Abstract Conclusion: After the reconstruction of imaging in dual-energy CT gemstone spectral imaging, the ratio of the two slopes curves, the target lymph node and primary lesion, respectively, might contribute to the clinical diagnosis of cervical lymph nodes in laryngeal and hypopharyngeal squamous carcinoma. Objective: To investigate the value of the dual-energy CT gemstone spectral imaging for clinical detecting of metastatic cervical lymph nodes in laryngeal and hypopharyngeal squamous carcinoma. Methods: Forty-seven cases who were suffering from laryngeal or hypopharyngeal squamous carcinoma and had complete clinical and pathological data were included, and 79 cervical lymph nodes were studied retrospectively (including 31 metastatic nodes and 48 non-metastatic nodes). Contrast-enhanced energy spectral imaging and reconstruction were performed. After the reconstruction, the slope of the curve in the target lymph node and the lesion were calculated. The ratio of the two slopes was studied. The pathological data of cervical lymph node and primary lesion were also collected. Results: The ratios were 1.20 ± 0.09 and 0.82 ± 0.12 in metastatic and non-metastatic lymph nodes, respectively. The difference was statistically significant (p < 0.05). The ratio was positively correlated to the stasis of lymph nodes only, rather than their morphological appearance, the pathological classification, or the individual difference (p < 0.05).